SOSIALISASI DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI KECAMATAN CAMBAI KOTA PRABUMULIH PROVINSI SUMATERA SELATAN - Anggleni, Andela (Jurnal Semarak Mengabdi, 2024)
The title of this service is Socialization in Improving the Quality of Public Services in Cambai District, Prabumulih City, South Sumatra Province. This service primarily aims to discuss and explain matters relating to Improving the Quality of Public Services in Cambai District, Prabumulih City, South Sumatra Province. The aim of this service is so that the public can know about improving the quality of public services. The results of the service show that improving the quality of public services has been implemented for village officials and religious, community leaders and youth leaders in Cambai District, Prabumulih City, South Sumatra Province. Thus, there is a significant relationship between improving the quality of public services and the effectiveness of carrying out tasks at the Cambai sub-district office, Prabumulih City, South Sumatra Province. To optimize this, it is necessary to add facilities such as adequate computer printers, internet networks and human resources who are trained according to needs, and personnel (HR) need to be given training and socialization to the community is also very much needed.